Rashba Spin Splitting in HgCdTe Quantum Wells with Inverted and Normal Band Structures - Svetlana V. Gudina; Vladimir N. Neverov; Mikhail R. Popov; Konstantin V. Turutkin; Sergey M. Podgornykh; Nina G. Shelushinina; Mikhail V. Yakunin; Nikolay N. Mikhailov; Sergey A. Dvoretsky (Nanomaterials, 2022)
In quantum wells (QWs) formed in HgCdTe/CdHgTe heterosystems with a variable composition of Cd(Hg), Shubnikov-de-Haas (SdH) oscillations are investigated to characterize the Rashba-type spin-orbit coupling in QWs with both a normal and inverted band structure. Several methods of extracting the Rashba spin-splitting at zero magnetic field and their magnetic field dependences from the beatings of SdH oscillations are used for greater reliability. The large and similar Rashba splitting (25–27 meV) is found for different kinds of spectrum, explained by a significant fraction of the p-type wave functions, in both the E1 subband of the sample with a normal spectrum and the H1 subband for the sample with an inverted one.